Sustainability, Human Well-Being, and the Future of Education - Cook, Justin W. (Springer Nature, 2019)
This open access book explores the key dimensions of a future education system designed to enable individuals, schools, and communities to achieve the twin twenty-first century challenges of sustainability and human well-being. For much of the twentieth century, Western education systems prepared students to enter the workforce, contribute to society and succeed in relatively predictable contexts. Today, people are at the controls of the planet-making decisions that are dramatically reshaping social, economic, and environmental systems at a global scale. What is education's purpose in this new reality? What and how must we learn now? The volatility and uncertainty caused by digitalization, globalization, and climate change weave a common backdrop through each chapter. Using case studies drawn from Finland and the US, chapter authors explore various aspects of learning and education system design through the lenses of sustainability and human well-being to evaluate how our understanding and practice of education must transform. Using their scholarly research and experience as practitioners, the authors propose new approaches to preparing learners for a new frontier of the human experience fraught with risks but full of opportunity.